The effects of hydrate formation and dissociation on the water-oil interface: Insight into the stability of an emulsion. (15th April 2020) - Guo, Dongdong; Ou, Wenjia; Ning, Fulong; Fang, Bin; Liu, Zhichao; Fang, Xiangyu; Lu, Wanjun; Zhang, Ling; Ud Din, Shahab; He, Zhongjin
Highlights: Effect of hydrate formation on the water-oil interface under extreme conditions are investigated for the first time. An oil-droplet chain is observed when hydrates rapidly form near the water-oil interface. A more profound conceptual model for hydrate-induced instability of oil-water emulsion is proposed. Abstract: Understanding of the stability of oil-dominated emulsion, such as the oil-based drilling fluids and crude oils, is of great importance to control the gas hydrate risk management when gas hydrates formation and dissociation occurs in the emulsion. Here, a high-pressure optical capillary cell with micro-Raman spectroscopy is utilized to investigate the effects of hydrate formation and dissociation on the stability of a simulated oil-water emulsion and the micro kinetics near the oil/water interface. Both the hydrate formation and dissociation processes are stimulated in water phase near the oil-water interface. The results show that the oil can enter the water phase from the oil phase with the oil-water interface failure when hydrates rapidly growth very close to the water-oil interface, even resulting in a series of oil droplets in the water phase (oil-droplet trajectory). The interesting phenomenon are mainly caused by the concentration gradient of methane and the Marangoni effect. Subsequently, the hydrate phase dissociates, a new stable water-oil interface presents when the system becomes rebalanced. The methane diffusion behavior induced by the chemical potential gradient in hydrate formation and dissociation processes could affect the stability of the emulsion. In addition, a more profound conceptual hydrate-induced destabilization model for different types of oil-water emulsions is proposed. This study can provide a theoretical and experimental basis for the safe implementation for deep-water oil and gas drilling, hydrate drilling in permafrost and multiphase mixing transportation in pipelines.